Hallazgos de la neurociencia que deberían ser conocidos y considerados en educación - Bringas González, Nataly (2014)
This article presents an overview of theimportance of the findings that havebeen made in the fields of neuroscience,such us attention, memory, emotion andlearning and aspects involved as brainneuroplasticity. It also presents some ofthe neuromyths circulating in educationalsettings.